Produksi Tanaman Kopi Arabika pada Beberapa Jenis Pohon Penaung - Rokhmah, Dewi Nur; Supriadi, Handi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Rokhmah DN, Supriadi H. 2022. Arabica Coffee Yield Under Several Types of Shade Trees. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 97-104. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Arabica coffee plantation in Perhutani land is generally under several types of shade trees, so the potential for soil fertility under each type of shade tree will be different. Differences in soil fertility in coffee plantations under several types of shade trees will cause variations in coffee yield. This study aimed to analyze the yield of Arabica coffee plants on several types of shade trees. The research was conducted in Pangalengan, Bandung Regency, West Java Province, from January to December 2020 using the survey method. The plant sample population was Arabica coffee grown under four types of shade trees, namely: pine (Pinus merkusii), red cedar (Toona sureni), tembusu (Fagraea fragrans), and rainbow eucalyptus (Eucalyptus deglupta). Determination of the research location was carried out purposively according to the type of plant that had been determined as a shade plant. Meanwhile, the determination of coffee plants as an example of observation was carried out by simple random sampling. The results showed that the litter of leda, suren, and tembusu trees has the potential to contribute quite a lot of organic matter seen from the production of litter per month which is quite high with high nutrient content and can decompose faster. While the pine shade has less litter and a longer decomposition process. The highest yield of Arabica coffee cherry was in the shade of Leda (4.82 kg/tree), then tembusu (3.86 kg/tree), pine (2.27 kg/tree), and suren (2.18 kg/tree).